Strength and bondability of a dental Y-TZP after silica sol-gel infiltrations. Issue 10 (July 2020) - Ramos, N.C.; Alves, L.M.M.; Ricco, P.; Santos, G.M.A.S.; Bottino, M.A.; Campos, T.M.B.; Melo, R.M.
Abstract: This study aimed to evaluate the effects of silica-dipping infiltration in zirconia, using sol-gel method, on flexural strength, short-term and long term bond strengths to resin cement, microstructure and surface characteristics. 330 specimens were made of zirconia (InCeram YZ, Vita Zahnfabrik) and divided into 6 groups: no infiltration (control); slow and fast (ammonium carbonate as catalyst): infiltrations with silicic acid obtained from sodium metasilicate, and infiltration with silicic acid obtained from TEOS. Fast infiltration was further performed second and third times. The disks were characterized using XRD, FT-IR and SEM and then submitted to a biaxial flexural test (BFT). To measure the shear bond strength (SBS test), zirconia specimens were superficially treated and bonded with resin cement. Specimens were tested either before and after thermal aging. BFT and SBS data in MPa were analyzed with one- or two-way ANOVA and Tukey (95%) tests. Weibull analysis was used to determine the structural homogeneity (95% CI). The infiltrated groups presented ZrSiO4 peaks, showing that the infiltration was effective. SEM images showed a homogeneous silica layer on the surface of all infiltrated groups, except those TEOS-infiltrated. The 2-immersion group presented improved structural homogeneity (higher Weibull modulus), including all the infiltrations with metassilicate, and 3-immersions (1104.4 MPa) and Control (1082.1 MPa) groups provided the highest strength. In groups without ageing, the slow infiltration (11.39 MPa) and the fast infiltration after 2 immersions (9.10 MPa) had higher bond strength values. After ageing, a significant decrease in bond strength was observed; the 3-immersion fast infiltration showed higher bond strength (5.77 MPa). Silica infiltration by the sol-gel method can be effectively applied in as little as 40 min with use of a catalyst. This method produces a zirconia with increased reliability that is suitable for adhesive bonding. The protocol presenting the best combination of flexural and bond strength was the 3 immersion-bath in silica sol.